Efforts to Improve the Performance of the State Security Unit of Intelkam in Investigations for the Prevention of ’LL’ Pill-Type Drugs at the Kediri City Police - Firmansyah, Libertino Banny (Advances in Police Science Research Journal, 2024)
This research presents an analysis of the problem of drug abuse, especially the ’LL’ pill type, which is disturbing the community in Kediri City. This research aims to understand and improve the performance of the Satintelkam State Security Unit in preventing drug trafficking, especially ’LL’ pills. In an effort to improve performance, this research describes the implementation of Satintelkam’s duties in drug investigations using Spencer’s (1993) competency theory, which includes knowledge, skills and attitudes. By considering these factors, the research analyzes how performance improvements can be made by Satintelkam in strengthening efforts to prevent the spread of drugs. The research results show that in terms of knowledge, Satintelkam members have extensive experience, but there are deficiencies in skills and attitudes. Many members have not received the necessary training and development, and the lack of personnel is also an obstacle. Apart from that, there is a need to improve more careful planning in carrying out tasks and strengthen cooperation with other units within the police, especially with the Narcotics Investigation. In conclusion, this study suggests adding personnel, increasing participation in training, better task planning, and increasing cooperation between units as steps to improve Satintelkam’s performance in preventing drug trafficking. It is hoped that this suggestion can contribute to overcoming the problem of drug abuse in Kediri City and provide guidance for further research and policy in this regard.